Isolation of genes (nif/hup cosmids) involved in hydrogenase and nitrogenase activities in Rhizobium japonicum. - Hom, S S (1985)
Recombinant cosmids containing a Rhizobium japonicum gene involved in both hydrogenase (Hup) and nitrogenase (Nif) activities were isolated. An R. japonicum gene bank utilizing broad-host-range cosmid pLAFR1 was conjugated into Hup- Nif- R. japonicum strain SR139. Transconjugants containing the nif/hup cosmid were identified by their resistance to tetracycline (Tcr) and ability to grow chemoautotrophically (Aut+) with hydrogen. All Tcr Aut+ transconjugants possessed high levels of H2 uptake activity, as determined amperometrically. Moreover, all Hup+ transconjugants tested possessed the ability to reduce acetylene (Nif+) in soybean nodules. Cosmid DNAs from 19 Hup+ transconjugants were transferred to Escherichia coli by transformation. When the cosmids were restricted with EcoRI, 15 of the 19 cosmids had a restriction pattern with 13.2-, 4.0-, 3.0-, and 2.5-kilobase DNA fragments. Six E. coli transformants containing the nif/hup cosmids were conjugated with strain SR139. All strain SR139 transconjugants were Hup+ Nif+. Moreover, one nif/hup cosmid was transferred to 15 other R. japonicum Hup- mutants. Hup+ transconjugants of six of the Hup- mutants appeared at a frequency of 1.0, whereas the transconjugants of the other nine mutants remained Hup-. These results indicate that the nif/hup gene cosmids contain a gene involved in both nitrogenase and hydrogenase activities and at least one and perhaps other hup genes which are exclusively involved in H2 uptake activity.